Birthright citizenship and education - Do immigrant children need a passport to thrive? - Christoph Sajons; Irma Clots-Figueras (ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2014)
This paper evaluates the effect of becoming citizen of the host-country at birth on educational outcomes of immigrant children in Germany. We exploit the introduction of birthright citizenship for newborn children in Germany starting on the 1st of January, 2000, to obtain difference-in-differences estimates for the effect of citizenship on the children s educational performance, in particular, their transition to different tracks of secondary school. Using data from the newly established National Education Panel Study (NEPS), the empirical results indicate an increase in the probability of migrant children to enter the middle school track rather than the lower one. This suggests that growing up with the citizenship of the host country has a beneficial impact on the later integration of migrant children.
Keywords: I21; J24; J15; 330